The long-term habituation of sexual arousal in human males: a crossover design. - Plaud, Joseph J.; Gaither, George A.; Henderson, Susan Amato (Psychological Record)
Short-term and long-term habituation of sexual arousal was investigated in a crossover design. Nine subjects completed six sessions semiweekly for 3 consecutive weeks. Sessions were scheduled at least 2 days but not more than 4 days apart. Each session consisted of 15 stimulus periods and 15 detumescence periods. Sexually explicit audio stimuli were administered. There were two conditions in the crossover design, which allowed each participant to serve as his own control. During one halt of the sessions subjects were exposed to 15 different scripts (varied condition); during the remaining sessions subjects were exposed to the same script 45 times (15 trials for each of three sessions, the constant condition). The constant stimulus condition was the experimental habituation condition, whereas the varied stimuli served as a control for physiological fatigue. Scripts were randomly assigned to stimulus conditions. Subjects showed systematic decreases in penile responding within the second and third constant stimulus conditions, but no systematic decreases were noted in any of the varied stimulus conditions. Subjects evidenced significant long-term decreases in physiological responding only in the constant stimulus condition as well as short-term decreases in subjective report of arousal. Long-term habituation of sexual arousal may be related to molar behaviors such as promiscuity and the spread of sexually transmitted diseases, and may be tied to sociobiological accounts of long-term sexual behavior patterns in human males. Reprinted by permission of the publisher.